Condensation of o-Phthalaldehydic Acid with Dihydroxy Benzenes, Part VII: Synthesis of 3-(Dihydroxyphenyl) Phthalides and their Nitration Reactions - Al-Hamdany, Raad; A. Fataftah, Zacharia (Asian Journal of Chemistry, 2010)
The condensation of o-phthalaldehydic acid (1) with hydroquinone, resorcinol and catechol in 30-55% H2SO4 afforded the corresponding 3-arylphthalide (2a, b, 3a) respectively, while with more concentrated acid > 70% they afforded the unisolated 1,3-diaryl isobenzofuran of type (4). Nitration of compound 2a–b, 3a–c with aqueous nitric acid/acetic acid mixture gave the corresponding mono-nitro derivative (5, 6a–d), but in one case the dinitro derivative(6e) was isolated. Some of these mono-nitro derivatives show acid-base indicator behaviour. The structures of isolated products were confirmed from their spectral and analytical data.